Comparative analysis of Microsoft Kinect Azure and manual measurement methods in the sit and reach test among elite female weightlifters - Usame Ömer Osmanoğlu; Kenan Erdaği; Bülent IŞIK; Serkan Örücü; Erkan Özbay (Scientific Reports)
Abstract Microsoft Kinect is an increasingly common tool for low-cost and portable measurement of human movements. The aim of this study was to investigate the potential reliability and reproducibility of Microsoft Kinect Azure in the sit-and-reach test conducted under standardized test conditions in a controlled training environment with elite female weightlifters. The sit-and-reach test was performed with Microsoft Kinect Azure and manual methods and also the reliability and validity were analyzed by comparing the wrist, elbow, shoulder and trunk joint angle measurements with the digital goniometer. Twenty-one healthy female weightlifter athletes who won medals in international championships were included in the study. Sit-and-reach testing was performed using Microsoft Kinect Azure and manual methods in accordance with the standards of the American College of Sports Medicine. The flexion range of motions of each athlete’s wrist, elbow, shoulder and trunk joint angles were measured with a digital goniometer and Microsoft Kinect Azure. Statistical analyses were performed using IBM SPSS 25.0 and Python 3.9.12 software. Descriptive statistics were calculated for all variables, and differences between Kinect and manual methods were evaluated with the Mann-Whitney U test and Wilcoxon Signed-Rank Test. Linear relationships between measurements were analyzed with Spearman correlation coefficients. Intraclass Correlation Coefficient was calculated for the concordance analysis and presented with Bland-Altman plots. The level of significance was accepted as p < 0.05. The findings suggest that Kinect Azure may provide good reproducibility and agreement with manual goniometric measurements for joint angles under the specific structured conditions tested. For parameters such as the elbow, shoulder, wrist, trunk angles and distance traveled, high ICC values (> 0.90) indicated strong consistency between the methods. Kinect Azure may serve as a reliable alternative to manual measurement methods under standardized testing conditions. Further studies are recommended to examine its generalizability to other populations and test environments.